2017
DOI: 10.1111/faf.12261
|View full text |Cite
|
Sign up to set email alerts
|

Fishery yields vary with land cover on the Amazon River floodplain

Abstract: Inland fisheries underpin food security in many tropical countries. The most productive inland fisheries in tropical and subtropical developing countries occur in large river–floodplain systems that are often impacted by land cover changes. However, few studies to date have assessed the effects of changes in floodplain land cover on fishery yields. Here, we integrated fisheries and satellite‐mapped habitat data to evaluate the effects of floodplain deforestation on fishery yields in 68 floodplain lake systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 78 publications
(119 reference statements)
3
42
0
Order By: Relevance
“…The correlation between flooded forest areas and their river types across the Amazon was less clear. Experimental gillnet studies and commercial fish landing analyses in different areas of the Amazon reported that fish abundance and/or diversity was most associated with flooded forest area (Arantes et al., ; Castello et al., ; Lobón‐Cerviá, Hess, Melack, & Araujo‐Lima, ). An experimental gillnet investigation of 15 floodplain lakes of the Central Amazon floodplain correlated fish species richness with the extent of shrub vegetation during the high water period and the extent of aquatic herbaceous communities and open waters during the low water season (Freitas et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation between flooded forest areas and their river types across the Amazon was less clear. Experimental gillnet studies and commercial fish landing analyses in different areas of the Amazon reported that fish abundance and/or diversity was most associated with flooded forest area (Arantes et al., ; Castello et al., ; Lobón‐Cerviá, Hess, Melack, & Araujo‐Lima, ). An experimental gillnet investigation of 15 floodplain lakes of the Central Amazon floodplain correlated fish species richness with the extent of shrub vegetation during the high water period and the extent of aquatic herbaceous communities and open waters during the low water season (Freitas et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The species‐specific regression results for three of the flagship characiform taxa, however, do not reflect the relative collinearity of floodplain lake and flooded forest area in the western Amazon because the large floodplain lake area of the eastern Amazon is not linearly correlated with fisheries production (Figure ). A more local study that focused on the eastern subregion indicated that floodplain forest cover was more correlated with fish yield than aquatic macrophytes associated with lakes (Castello et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, present legislation offers only scant protection for these floodplains. In Brazil, for example, floodplain protection is mostly based on the Forest Code, which only protects a maximum of 500 m of floodplain adjacent to river channels even though Amazonian floodplains often extend for tens of kilometres (Castello et al, ). Increased levels of protection for the land cover of floodplains may be needed to decrease the vulnerability of floodplain fishes, and this topic warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical river floodplain ecosystems are home to myriads of fish species, but they have been under growing human pressures (Junk, ; Tockner & Stanford, ). Large expanses of tropical floodplains have undergone land cover changes, especially deforestation (Renó, Novo, Suemitsu, Rennó, & Silva, ), which are linked to fish population declines (Castello et al, ; Arantes et al, 2018). In addition, fishing activities have overfished and depleted several floodplain fish populations (Castello et al, ; Coomes, Takasaki, Abizaid, & Barham, ).…”
Section: Introductionmentioning
confidence: 99%